Analyzing the environmental role of resource efficiency, economic globalization, and biomass usage in Malaysia: a time-varying causal approach - Awosusi, Abraham Ayobamiji; Eweade, Babatunde Sunday; Ojekemi, Opeoluwa Seun (Springer Science and Business Media B.V., 2024)
Malaysia’s commitment towards sustainable environment requires implementing clean energy sources and less raw materials usage, which could have a significant impact on the nation’s biocapacity and ecological footprint. As a result, this study examined the environmental impact of resource efficiency, biomass energy, and economic growth in Malaysia, within the load capacity curve hypothesis framework, while controlling economic globalization, financial globalization and trade globalization. This research utilizes the ARDL estimator and the bootstrapped time-varying causality (TVC) approach to analyse the dataset from 1970 to 2018. The findings of the ARDL estimator reveals that biomass energy and resource efficiency increase load capacity factor (LF), while trade globalization reduces LF in Malaysia. Furthermore, the result uncovered the validity of the load capacity curve hypothesis, highlighting that the persistent economic activities will help to achieving ecological quality in Malaysia. The result of the bootstrapped TVC approach reveals a feedback causal association between LF and its predictors in Malaysia. These results emphasize the need for an effective circular economy, which involves maximizing resource use, reducing waste, and incorporating biomass energy into this framework. © The Author(s) 2024.
Keywords: Biomass energy; Economic globalization; Load capacity curve hypothesis; Malaysia; Resources efficiency